Factores biosociales y nivel de conocimiento sobre planificación familiar de los adolescentes de la Institución Educativa Toribio Rodriguez de Mendoza. Huamachuco - 2009 - Briceño Sevillano, Luis Camilo (2009)
Show it quantitative fellow's investigation transverse- cut correlational had success in district of Marcabalito's, Provincie's of Sánchez Carrión with the objective of determining the relation among the factors biosociales: Age, sex and procedence and; The knowledge level on family planning in her teens in the high school Toribio Rodríguez of Mendoza The sign was constituted for 151 teens whom were applied an opinion poll to determine the knowledges level on family planning. Following conclusions were reached: He found the teens's 76.8 percent of the under consideration population's the whole they have among 14 and 16 years, the 52.3 percent they belong to the masculine sex, and the 84.1 percent they come from the rural zone. In relation to knowledges level the 75.5 percent he caught up with a regular level, in point than the 18.5 percent deficient level and only the 4.0 percent he caught up with a good- knowledge level. The test statistical he yielded that significant relation among the factors does not exist age, sex and procedence and, the know-ledges level on family planning of her teens Mendoza's high school Toribio Rodríguez of Mendoza.